Gothic fiction and the writing of trauma, 1914 -1934 : the ghosts of world war one - Smith, Andrew, 1964- (Edinburgh : Edinburgh University Press, 2022)
The first detailed analysis of literature and trauma in World War OneExplores how the Gothic shaped, and controlled, cultural anxieties about the warProvides a unique critical revision of the figure of the ghost across a wide range of literature of the periodDraws on the Imperial War Museum's archives (especially for accounts of the war by less-well-known figures Dorothea Crewdson, Jack Martin and Ronald Skirth)Critically complicates the view of the Gothic as articulating, rather than containing, traumaThis book examines the representation of the ghost-soldier in literature published from 1914-1934, both marking the presence of trauma and attempting to make sense of trauma. Andrew Smith examines short stories, novels, poems and memoirs that employ ghosts to reflect upon feelings of loss, paralleling the literary context with accounts of shell-shock which construe the damaged soldier as psychologically missing and therefore spectre-like.The author argues that literary and non-literary texts repeatedly deploy a form of the uncanny, familiar from a Gothic tradition, as way of reflecting upon grief. In support of this claim, he draws on fiction by well-known authors such as M. R. James, E. F. Benson, Dorothy L. Sayers, and Dennis Wheatley, alongside largely forgotten contributions to The Strand and other periodical publications such as The Occult Review.
Frontmatter -- Contents -- Acknowledgements -- Introduction: The Ghosts of War -- 1 The Psychology of War: Gothic and the Redirection of the Uncanny -- 2 The Ghosts of War: Writing Trauma -- 3 Spiritualism, War and the Modernist Gothic -- 4 Aftershock: Malevolent Ghosts and the Problem of Memory -- Conclusion: Ghostly Afterlives -- Bibliography -- Index
Includes bibliographical references and index.
Description based upon online resource; title from PDF title page (viewed July 11th, 2022).
JSTOR
Keywords: Gothic fiction (Literary genre), English -- History and criticism; World War, 1914-1918 -- Literature and the war; Supernatural in literature; English fiction -- 20th century -- History and criticism; Surnaturel dans la littérature.; Roman anglais -- 20e siècle -- Histoire et critique; HISTORY / Military / World War I; LITERARY CRITICISM / General; English fiction; Gothic fiction (Literary genre), English; Supernatural in literature; War and literature; Inter-war period c 1919 to c 1939.; Literature: history & criticism; Literary theory; Literature; 1900-1999; Criticism, interpretation, etc